Do you truly feel pleasant? The effect of question formulations on affective responses to acute exercise - Zhang, Qi (Frontiers in Psychology, 2025)
The current study used the Feeling Scale, developed by Hardy and Rejeski, to examine how question formulations affect affective responses during acute exercise. A within-group experimental design of 3 (question formulations) × 6 (measurement time) was used. The three types of question formulations were positive, negative, and neutral. The measurement time was divided into three categories: prior to the beginning of the exercise, at 5-min intervals during the exercise, and immediately following the cool-down, resulting in a total of 6 measures. Participants’ heart rate was tracked throughout, and affective responses were evaluated using one question formulation per exercise, in a random order. We recruited 21 college students to complete three 30-min moderate-intensity running sessions (2 days apart). A repeated-measures ANOVA treated question formulations and measurement time as independent variables. Results showed that: (1) When ratings of affective responses were the dependent variable, the main effect of measurement time (F(1.726, 34.522) = 8.043, ηp2 = 0.287, p < 0.01) and question formulation (F(1.928, 38.567) = 6.382, ηp2 = 0.242, p < 0.01) were significant, and the interaction between the two was significant (F(3.873, 77.461) = 3.552, ηp2 = 0.151, p < 0.05). Simple effects analyses showed that affective responses in positive question formulations were superior to those in negative, but not significantly distinct from those in neutral. Neutral question formulations got better affective responses than negative question formulations. (2) For SDNN and RMSSD, the main effect of measurement time was significant (F(2.514, 50.270) = 30.739, ηp2 = 0.606, p < 0.001; F(2.115, 42.307) = 44.041, ηp2 = 0.688, p < 0.001). Acute exercise led to notable drops in SDNN and RMSSD, indicating acute exercise significantly reduced both parameters. Neither the main effect of question formulation nor the interaction was significant. Question formulations influenced affective responses: positive and neutral formulations elicited better affective responses than negative formulations.